(untitled) (LEGAL DIALOGICA, 2025)
This study aims to examine the legal status of inheritance rights for children out of wedlock under the indonesian civil law, as well as to identify the development of jurisprudence and the impact of the Constitutional Court’s decision on the civil rights of such children. This resarch employs a normative legal research method, utilizing statutory, case, and literature apporaches, and involves both primary and secondary legal materials, such as legislation, legal doctrines, and relevant academic journals. The findings indicate that under the Indonesian Civil Law, out of wedlock children are granted limited inheritance rights. The legal position of such children under Law No. 1 of 1974 on Marriage is also discussed. However, legal developments particulartly the Constitutional Court Decision No. 46/PUU-VIII/2010 have opened the possibility for out of wedlock children ti inherit from their biological fathers, provided that biological relationship can be legally proven. This study recomends the necessity of harmonizing civil law, Islamic law, and human rights principles in order to ensure the protection of the best interests of the child. Abstrak: Penelitian ini bertujuan untuk mengkaji kedudukan hukum hak waris anak luar nikah menurut Kitab Undang-Undang Hukum Perdata (KUHPerdata), serta mengidentifikasi perkembangan yurisprudensi dan pengaruh putusan Mahkamah Konstitusi terhadap hak-hak keperdataan anak luar nikah. Menggunkan metode penelitian normative, dengan pendekatan terhadap peraturan perundang-undangan, pendekatan kasus, dan studi pustaka yang melibatkan bahan hukum primer dan sekunder seperti undang-undang literatur, dan jurnal terkait. Hasil penelitian menunjukkan bahwa menurut KUHPerdata, anak luar nikah memiliki keterbatasan hak waris, bagaimana kedudukan anak luar nikah menurut UU No. 1 Tahun 1974, namun perkembangan hukum melalui Putusan Mahkaman Konstitusi No. 46/PUU-VIII/2010 membuka peluang bagi anak luar nikah untuk memperoleh hak waris dari ayah biologisnya sepanjang dapat membuktikan secara sah. Penelitian ini merekomendasikan perlunya harmonisasi antara hukum perdata, hukum Islam, dan hak asasi manusia untuk melindungi kepentingan terbaik anak.